Development of Survey Methods to Effectively Sample Juvenile Red Snapper along the Atlantic Coast of Florida. Issue 5 (8th August 2022) - Brodie, Russell B.; Solomon, Justin J.; Paperno, Richard; Switzer, Theodore S.; Swanson, Christopher E.
Abstract: Understanding of the early life history of Red Snapper Lutjanus campechanus throughout the U.S. Atlantic Ocean (hereafter, "Atlantic") is limited, in part, due to the paucity of juveniles (<150 mm TL) collected in long‐term fishery‐independent surveys in the region. This is in sharp contrast to the Gulf of Mexico (hereafter, "Gulf"), where juvenile Red Snapper have been consistently collected in surveys. This apparent regional disparity is poorly understood. Red Snapper nursery habitats may differ between the Atlantic and the Gulf, previous Atlantic surveys may not have included important nursery habitat, or sampling gear used in the Atlantic may not be effective at collecting juveniles. A 2‐year fishery‐independent study was conducted along the Atlantic coast of Florida to test whether juvenile Red Snapper could be effectively sampled with two types of gear not commonly used there: a semi‐balloon trawl like those used in long‐term groundfish surveys in the Gulf and small‐mesh Z‐traps. In total, 194 Red Snapper were collected in the trawl samples and 202 Red Snapper were collected in the Z‐trap samples—mostly juveniles (age 0 and age 1) captured in nearshore waters (<30 m deep). Like the Gulf, shallow coastal waters in the Atlantic likely function as nursery habitat for Red Snapper. Primarily small age‐0 Red Snapper were collected during trawl sampling, which targeted unconsolidated nonreef habitats, whereas larger age‐0 and age‐1 and older Red Snapper were collected during trap sampling, which targeted hard‐bottom reef habitats. Although this study represents the most successful sampling of juvenile Red Snapper in the Atlantic to date, further research is required to delineate the northern and southern extents of Red Snapper nursery grounds. Nevertheless, our results provide a framework for developing a fishery‐independent survey that targets juvenile Red Snapper in the Atlantic to provide valuable data for quantifying recruitment and monitoring the status and recovery of this economically important species.